Assessment of carbamazepine removal from hospital wastewater in a non conventional biofilter and the application of electro-oxidation as pre-treatment - Navarro-Franco, Javier Alejandro; Garzón-Zúñiga, Marco A.; Drogui, Patrick; Barragán-Huerta, Blanca Estela; Vigueras-Cortés, Juan Manuel; Lozano-Guzmán, Eduardo; Moreno-Cruz, Francisco Javier (Tecnología y ciencias del agua, 2024)
Hospital wastewater (HWW) is characterized by a high drug concentration, which can cause endocrine effects and bacterial resistance, among others. For this study, carbamazepine (CBZ) was selected as a contaminant model to evaluate the removal efficiency from HWW of recalcitrant pharmaceuticals in a non‑conventional biofilter (BF), packed with a mixture of wood chips (Prosopis) and porous rock (pouzzolane). The effect of electro-oxidation (EO) as pre-treatment was assessed as well. A biofilm adapted to the HWW was developed in the BF. The addition of high concentrations of CBZ (1 000 and 10 000 µg/l) to the influent HWW did not affect the removal efficiency of the BF to remove organic matter (73 %) and ammonia nitrogen (99 %), proving that the biomass was not inhibited by the CBZ's concentration. The BF showed a significant removal of CBZ by adsorption during the start‑up. The bed filter showed an adsorption capacity of 19.84 µg/g (Co = 10 000 µg/l). After the bed filter saturation operated in steady state, the BF removed by biotransformation 17.2 ± 7.4 % of CBZ which, in terms of concentration (1 551 ± 664 µg/l), is bigger than the concentration in most of the reports for hospital, pharmaceutical and municipal WW effluents, which are between 0.1 and 890 µg/l. By applying electro-oxidation as a pretreatment, the global removal efficiency of CBZ increased to 55 ± 5.96 %. In the hybrid system, the EO biotransformed the CBZ, and in the BF the nitrogen and the COD were removed and showed CBZ desorption.